Optimizing Carrageenan-Based Moisturizers: From Kappaphycus alvarezii Extraction to Formulation - Suci, Nurul; Rahmi, Alfia; Nasri, Nasri; Kaban, Vera Estefania (Talenta Publisher, 2025)
Carrageenan, a sulfated polysaccharide extracted from red seaweed (Kappaphycus alvarezii), possesses a high water-holding capacity and has been widely investigated for its potential application as a skin moisturizing agent. This study aimed to formulate isolated carrageenan into a topical cream and to evaluate its physicochemical characteristics and moisturizing efficacy. Carrageenan was isolated through sequential soaking, decantation, extraction, isolation, drying, and milling processes. The isolated material was characterized in terms of solubility, viscosity, loss on drying, and Fourier transform infrared (FTIR) spectroscopy. Cream formulations containing carrageenan at concentrations of 2.5%, 5%, 7.5%, and 10% (w/w) were prepared and compared with a 2% glycerin cream and a blank control. Physical quality evaluations included homogeneity, pH, emulsion type, stability testing for 12 weeks, skin irritation assessment, and in vivo moisturizing activity in 18 human volunteers. The isolated carrageenan complied with the requirements of USP XXX. All carrageenan-based creams exhibited acceptable homogeneity, skin-compatible pH, and satisfactory physical stability throughout the storage period. No signs of skin irritation were observed. Moisturizing efficacy increased proportionally with carrageenan concentration, with the 2.5% carrageenan cream demonstrating a moisturizing effect comparable to that of the 2% glycerin formulation. These findings support the potential of carrageenan derived from Kappaphycus alvarezii as an effective natural moisturizing agent in topical cream formulations.